Determinação turbidimétrica de dipirona em fluxo utilizando um reator contendo cloreto de prata imobilizado em resina poliéster - Marcolino-Jr., Luiz H.; Bonifácio, Viviane Gomes; Fatibello-Filho, Orlando; Teixeira, Marcos F. S. [UNESP] (Sociedade Brasileira de Química, 2005)
A simple flow injection procedure was developed for determining dipyrone (1-phenyl-2,3-dimethyl-4-methylaminomethano-5-pyrazolone sodium, metamizol, analgin) in pharmaceutical formulations. The determination is based on the reduction of Ag+ ions to Ag0 by dipyrone. A colloidal suspension of Ag0 produced was transported by carrier solution (0.01 mol L-1 NaOH) and turbidimetrically detected at 425 nm. The analytical curve for dipyrone was linear in the range from 5.0 x 10-4 to 2.5 x 10-3 mol L-1 with a correlation coefficient of 0.9990. The detection limit was 1.3 x 10-4 mol L-1 (3sigmaB/slope). The relative standard deviation for ten successive measurements was 1.8% and an analytical frequency of 45 h-1 was obtained. The recovery values from three samples ranged from 96.0 to 102%.
Flow injection turbidimetric determination of dipyrone using a solid-phase reactor containing silver chloride immobilized in a polyester resin
Keywords: dipyrone; flow injection turbidimetry; solid-phase reactor